2021
DOI: 10.1021/acsptsci.1c00080
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Severe Acute Respiratory Syndrome Coronavirus 2 Replication by Hypertonic Saline Solution in Lung and Kidney Epithelial Cells

Abstract: An unprecedented global health crisis has been caused by a new virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We performed experiments to test if a hypertonic saline solution was capable of inhibiting virus replication. Our data show that 1.2% NaCl inhibited virus replication by 90%, achieving 100% of inhibition at 1.5% in the nonhuman primate kidney cell line Vero, and 1.1% of NaCl was sufficient to inhibit the virus replication by 88% in human epithelial lung cell line Calu-3. Fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 67 publications
1
23
0
4
Order By: Relevance
“…Hyponatremia where plasma sodium concentration is below 135 mmol/L is often associated with viral infections including COVID-19 [ 422 ]. Furthermore, in vitro experiments found 1.5% NaCl solution can achieve 100% inhibition of SARS-CoV-2 replication in nonhuman primate kidney Vero cells, while 1.1% of NaCl can inhibit viral replication by 88% in human epithelia lung Calu-3 cells [ 423 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…Hyponatremia where plasma sodium concentration is below 135 mmol/L is often associated with viral infections including COVID-19 [ 422 ]. Furthermore, in vitro experiments found 1.5% NaCl solution can achieve 100% inhibition of SARS-CoV-2 replication in nonhuman primate kidney Vero cells, while 1.1% of NaCl can inhibit viral replication by 88% in human epithelia lung Calu-3 cells [ 423 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…The major mechanism is possibly through sodium ion-mediated intracellular low energy states [15]. In this study, we observed that hypertonic saline can significantly block SARS-CoV-2specific FCS cleavage caused by furin but not by trypsin.…”
Section: Discussionmentioning
confidence: 56%
“…The major mechanism was possibly through sodium ion-mediated intracellular low energy states. 16 In this study, we observed that in both the wildtype and mutants, hypertonic saline could significantly block the SARS-CoV-2-specific FCS cleavage caused by furin but not by trypsin. As S protein cleavage played a critical role in the SARS-CoV-2 activation before entry into and exiting from the cells, the inhibitory effect of hypertonic saline on the SARS-CoV-2 replication could be at least partly due to the blockage of the furin-mediated cleavage.…”
Section: Discussionmentioning
confidence: 61%